Engineering Education in Sub-Saharan Africa: Quest for Quality - Mohamedbhai, Goolam (International Journal of African Higher Education, 2016)
Africa has huge potential for growth and development and its youthful population and abundant natural resources are key aspects that need to be fully exploited. Engineering is one area that requires specific attention as it provides highly skilled personnel for industrial development. Through essentially desktop research, this paper surveys the challenges that Sub-Saharan Africa faces in promoting engineering, such as lack of engineering capacity, shortage of engineering technicians, poor quality and relevance of educational provision, lack of human and financial resources, and poor linkages with industry. The paper then identifies several regional initiatives to address some of these challenges. Most of these are fairly recent and have yet to develop, and while several of them encourage harmonisation of approaches and collaboration among African institutions, hardly any place emphasis on university-industry linkages. Accreditation of engineering qualifications in Africa is key to improving the quality of the awards. Only a few African countries have established a really robust accreditation system for engineering qualifications. This paper suggests that these countries should take the lead in assisting the other countries, on a sub-regional basis, to improve their accreditation system, the ultimate goal being to establish a Pan-African engineering accreditation system. L’Afrique a un immense potentiel de croissance et de développement; sa jeune population et ses abondantes ressources naturelles en sont des aspects clés qui doivent être pleinement exploités. L’ingénierie est un domaine qui requiert une attention particulière puisqu’il permet de former du personnel hautement qualifié dans le but de développer l’industrie. Basé sur une recherche informatique, cet article analyse les défis rencontrés par l’Afrique sub-saharienne dans sa promotion de l’ingénierie – notamment le manque de capacité dans le domaine, la pénurie d’ingénieurs techniciens, l’enseignement inadapté et de médiocre qualité, le manque de ressources humaines et financières ainsi que le manque de liens avec l’industrie. Cet article identifie ensuite plusieurs initiatives régionales qui tentent de remédier à ces problèmes. La plupart sont récentes et ont encore besoin de se développer. Tandis que certaines de ces initiatives encouragent l’harmonisation des approches et la collaboration entre les institutions africaines, peu mettent l’accent sur les liens entre l’université et l’industrie. L’accréditation des diplômes d’ingénieur en Afrique est aussi essentielle pour améliorer la qualité de la formation. Seuls quelques pays africains ont réussi à mettre en place un système d’accréditation rigoureux pour les diplômes d’ingénieur. Cet article propose que ces pays jouent un rôle moteur à l’échelle sous-régionale et aident les autres pays à améliorer leur système d’accréditation – l’objectif ultime étant la mise en place d’un système d’accréditation panafricain pour les études d’ingénierie.